The 'Laterculus Malalianus' and the school of Archbishop Theodore - Stevenson, Jane 1959- (Cambridge studies in Anglo-Saxon England, 1995)
The Laterculus Malalianus, a historical exegesis of the life of Christ, appears to be the only complete text to survive from the hand of Archbishop Theodore at Canterbury. Its language, style and intellectual frame of reference are thus of great importance for establishing the nature and scope of teaching at Canterbury, the first school of Anglo-Saxon England. This edition, with translation and commentary, is the third volume in this series to offer a reassessment of Canterbury as a major seat of learning, together with Bernhard Bischoff's and Michael Lapidge's edition of the biblical commentaries from the Canterbury school and Michael Lapidge's edited collection of essays on the life and influence of Archbishop Theodore. In the introduction Jane Stevenson examines the intellectual milieu of this work, argues the case for attribution to Theodore, and suggests the need for a complete rethinking of the basis of Anglo-Saxon culture